2014
DOI: 10.1007/s00259-014-2821-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparing amyloid-β deposition, neuroinflammation, glucose metabolism, and mitochondrial complex I activity in brain: a PET study in aged monkeys

Abstract: (18)F-BCPP-EF could be a potential PET probe for quantitative imaging of impaired MC-I activity that is correlated with Aβ deposition in the living brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 39 publications
1
63
1
Order By: Relevance
“…18 F-fluorobenzyl triphenylphosphonium cation was reported to bind to mitochondria, reflecting their membrane potential with voltage-dependency (21); however, this PET probe has not been applied for imaging of mitochondrial function in the living brain. In contrast, our previous reports demonstrated the first PET probe as 18 F-BCPP-EF for MC-I imaging in the living brain (6)(7)(8).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…18 F-fluorobenzyl triphenylphosphonium cation was reported to bind to mitochondria, reflecting their membrane potential with voltage-dependency (21); however, this PET probe has not been applied for imaging of mitochondrial function in the living brain. In contrast, our previous reports demonstrated the first PET probe as 18 F-BCPP-EF for MC-I imaging in the living brain (6)(7)(8).…”
Section: Discussionmentioning
confidence: 74%
“…In addition to dopamine, we recently designed a PET probe, 2-tert-butyl-4-chrolo-5-{6-[2-(2-18 F-fluoroethoxy)-ethoxy]-pyridin-3-ylmethoxy}-2H-pyridazin-3-one ( 18 F-BCPP-EF), for the quantitative imaging of MC-I in vivo and confirmed that it was suitable for imaging MC-I function in the living brains of rats (6) and monkeys (7,8).…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…This is particularly true for Alzheimer's disease which is characterized by the presence of extracellular senile plaques, mainly composed of amyloid‐β (Aβ) peptide and intracellular neurofibrillary tangles made up of hyperphosphorylated tau protein (Selkoe, 2004). Several studies demonstrate that the Aβ peptide accumulates progressively into mitochondria (Hansson Petersen et al., 2008; Manczak et al., 2006) where it inhibits the activities of the respiratory chain complex and thus oxidative phosphorylation ( Hernandez‐Zimbron et al., 2012; Lahmy, Long, Morin, Villard, & Maurice, 2015; Tillement, Lecanu, & Papadopoulos, 2011; Tsukada et al., 2014). The Aβ peptide can also potentially cause mPTP opening in vivo as it induces mitochondrial swelling, decreases mitochondrial membrane potential, and potentiates the effect of mPTP inducers in isolated brain mitochondria (Du et al., 2008; Moreira, Santos, Moreno, & Oliveira, 2001; Shevtzova, Kireeva, & Bachurin, 2001).…”
Section: Evidence For the Involvement Of Mptp Opening In Age‐associatmentioning
confidence: 99%